Building Family Resilience Through Inspirational Parenting Seminars - Eva Siti Faridah; Muhammad Faqih Adzkia (Al-Qalam Institute, 2025)
Many parents are still unaware of the strengths and unique aspects of their children's development. A limited number of experts available for consultation on child development is one of the causes of issue. This research aims to explore the impact of a parenting seminar focusing on enhancing parents' understanding of Islamic parenting values. A qualitative Participatory Action Research (PAR) method was used, involving observations, interviews, and community engagement to gather data from parents, PKK mothers, and local youth. The seminar was found to successfully increase participants' understanding of Islamic parenting values, particularly those exemplified by the Prophet Muhammad SAW. The seminar also reinforced the role of parents as primary educators, emphasizing the shared responsibility of both parents in child-rearing. However, challenges in raising awareness and increasing participation were noted, suggesting the need for more effective communication strategies. This study contributes to the growing body of literature on community-based parenting education and highlights the importance of incorporating cultural and religious frameworks. Future seminars should focus on increasing accessibility and deepening content relevance.